2007
DOI: 10.1111/j.1540-5826.2007.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting First‐Grade Math Achievement from Developmental Number Sense Trajectories

Abstract: Number sense development was tracked from the beginning of kindergarten through the middle of first grade, over six time points. Children (n = 277) were then assessed on general math achievement at the end of first grade. Number sense performance in kindergarten, as well as number sense growth, accounted for 66 percent of the variance in first-grade math achievement. Background characteristics of income status, gender, age, and reading ability did not add explanatory variance over and above growth in number se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
403
5
36

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 473 publications
(491 citation statements)
references
References 40 publications
25
403
5
36
Order By: Relevance
“…In a first step of analysis, we were able to replicate core findings of previous longitudinal studies that found substantial correlations not only between early quantity-number competencies and math performance in school (see Aunola et al, 2004;Gersten et al, 2005;Jordan et al, 2007;Koponen, Aunola, Ahonen, & Nurmi, 2007;Krajewski & Schneider, in press;Passolunghi, et al, 2007;Stern, 1997Stern, , 1999, but also between early phonological awareness and math school performance (e.g., Alloway et al, 2005;Bradley & Bryant, 1985;Hecht et al, 2001;Koponen, Aunola, Ahonen, & Nurmi, 2007;Leather & Henry, 1994;Simmons, Singleton, & Horne, 2008). The latter were comparable in size with correlations between phonological awareness and subsequent literacy achievement in school found in studies on literacy development (e.g., Schneider & Näslund, 1999).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In a first step of analysis, we were able to replicate core findings of previous longitudinal studies that found substantial correlations not only between early quantity-number competencies and math performance in school (see Aunola et al, 2004;Gersten et al, 2005;Jordan et al, 2007;Koponen, Aunola, Ahonen, & Nurmi, 2007;Krajewski & Schneider, in press;Passolunghi, et al, 2007;Stern, 1997Stern, , 1999, but also between early phonological awareness and math school performance (e.g., Alloway et al, 2005;Bradley & Bryant, 1985;Hecht et al, 2001;Koponen, Aunola, Ahonen, & Nurmi, 2007;Leather & Henry, 1994;Simmons, Singleton, & Horne, 2008). The latter were comparable in size with correlations between phonological awareness and subsequent literacy achievement in school found in studies on literacy development (e.g., Schneider & Näslund, 1999).…”
Section: Discussionsupporting
confidence: 58%
“…The phonological loop and central executive were not included in the latent variable model because only one indicator each was available to represent these variables. According to our assumptions, QNC Level-I competencies should predict QNC at higher levels (when number words are linked with quantity; see Krajewski, 2008;Passolunghi et al, 2007), and these should predict later mathematical achievement in Grade 3 (see Gersten et al, 2005;Jordan et al, 2007;Koponen et al, 2007;Stern, 1999). We expected early phonological awareness (measured at T 1 ) to predict the development of QNC Level-I competencies (at T 2 ), but not to predict higher levels of QNC (isolated number-words hypothesis).…”
Section: Impact Of Visual-spatial Sketch Pad and Phonological Awarenementioning
confidence: 92%
See 1 more Smart Citation
“…At that age, Finnish children do not receive diagnoses for either math or reading difficulties. However, according to several longitudinal studies, the differences in the early number skills between low-and typically-performing children is notable, and this gap tends to grow in the following years (the Matthew-effect) (e.g., Jordan et al, 2007;Kohli et al, 2015). Children with low early number skills at the beginning of kindergarten (pre-primary education in the Finnish context) do not seem to benefit from instruction in the same way as their age-peers Jordan et al, 2006).…”
Section: Risk For Mathematics Difficultiesmentioning
confidence: 99%
“…Inter-individual differences in early number skills performance appears to be highly stable from kindergarten (called pre-primary education in the Finnish context) to later primary grades in both international (Jordan, Kaplan, Locuniak, & Ramineni, 2007;Kohli, Sullivan, Sadeh, & Zopluoglu, 2015; and national research (e.g., for review see also Mazzocco & Räsänen, 2013). Differences between low-and typically-performing children can already be seen in the pre-primary year (recently Aunio, Heiskari, van Luit, & Vuorio, 2015).…”
Section: Introductionmentioning
confidence: 99%